Medicinal Plants Used in the Siddha System of Medicine in Kalagam, Kaithady: Documentation, Botanical Identification - Miraaj, R.; Sujeethasai, K.; Vidhya, M.P. (University of Jaffna, 2026)
The Siddha system of medicine, widely practiced in South India and Sri Lanka, extensively uses medicinal plants for treating various ailments. Kalagam village in Kaithady harbors rich ethnomedicinal knowledge, yet systematic documentation of its medicinal flora is limited. This study aimed to document, classify, and analyze medicinal plants used in Siddha medicine, focusing on botanical families, plant habit, Siddha pharmacological attributes (Suvai, Veerya, Vipakam), therapeutic applications, and endemic status. A descriptive cross-sectional ethnobotanical survey was conducted among elderly informants with traditional knowledge. Data were collected through field observations and transect walks, including local names, plant parts used, ailments treated, and preparation methods. Botanical identification was performed using herbarium comparisons, and expert consultation. Descriptive statistics summarized family-wise distribution, habit, lifespan, and Siddha pharmacological attributes. A total of 105 species belonging to 52 families were documented. Fabaceae was the most represented family, followed by Asclepiadaceae, Euphorbiaceae, Malvaceae, and Amaranthaceae. Shrubs (37) and herbs (31) predominated. Bitter taste (Suvai) and hot potency (Veerya) were most common, while pungent post-digestive effect (Vipakam) predominated. Gastrointestinal, skin, and urinary disorders were the most treated ailments. Four endemic species Vernonia zeylanica, Plumbago zeylanica, Phoenix zeylanica, and Capparis zeylanica and high-value multipurpose species were identified. Leaves were the most frequently used plant part, reflecting sustainable practices. This study highlights the rich ethnomedicinal diversity of Kalagam, Kaithady in Northern provine of Sri Lanka and provides a foundation for future pharmacological validation and conservation of high-value and endemic medicinal plants.
Keywords: Siddha medicine; Medicinal plants; Ethnobotany; Kalagam; Suvai; Veerya; Vipakam; Endemic species